### Solving quadratics of the form x^{2} + bx + c = 0 − using the quadratic formula

Solving quadratics of the form ax^{2} + bx + c = 0 using the quadratic formula:

x = |

In the examples that follow a is always equal to 1

#### Example 1. Solve x

^{2}+ 7x + 6 = 0#### Example 2. Solve x

^{2}− 11x + 30 = 0#### Example 3. Solve x

^{2}+ 2x − 8 = 0#### Example 4. Solve x

^{2}− 5x − 24 = 0

x^{2} + 7x + 6 = 0 here a = 1, b = 7 and c = 6

Verify by putting these two values of x into x^{2} + 7x + 6

x^{2} − 11x + 30 = 0 here a = 1, b = − 11 and c = 30

Verify by putting these two values of x into x^{2} − 11x + 30

x^{2} + 2x − 8 = 0 here a = 1, b = 2 and c = − 8

Verify by putting these two values of x into x^{2} + 2x − 8

x^{2} − 5x − 24 = 0 here a = 1, b = − 5 and c = − 24

Verify by putting these two values of x into x^{2} − 5x − 24

to: